Obstetric violence in the perception of parturents: a scope review - Gonzaga, Márcia Féldreman Nunes (2022)
Childbirth is an important process in a woman's life, where it transforms her life. This process was not considered a medical procedure, as it occurred freely in the family environment. But over the years there was a change in this aspect, where childbirth came to be considered a procedure performed by the health team in hospitals. From this, the literature shows us that in this process, there was a disregard for the needs of the parturient, characterized by obstetric violence, considering the set of different types of violence and damage during professional care during childbirth, which can be an experience traumatic in a woman's life. The objective of the study was to identify in the literature the perception of parturients about obstetric violence in labor and delivery. The study was designed as a review of the scope, where the following guiding question was established: "What is the perception of pregnant women about obstetric violence in labor and delivery?" The method used for data collection is a bibliographic survey, through the electronic search for articles, which considered only scientific studies published in Portuguese, English and Spanish in the period from 2016 to 2021. As a result, the main perceptions of the parturients were: routine episiotomy or without consent; restricted perception of the concept of obstetric violence or ignorance of the term; Kristeller's maneuver; use of medication to induce childbirth; without permission to choose a position during childbirth and deprivation of the companion's freedom. However, it is concluded that episodes of obstetric violence are very common, but the perception of mothers is limited and restricted, without knowledge of the term. The subject is little understood as a violent act, for lack of knowledge.